Haptic industrial robot control with variable time delayed bilateral teleoperation - Soyguder, Servet; Abut, Tayfun (Emerald Group Publishing Ltd, 2016)
Purpose - This study attempts to control the movement of industrial robots with virtual and real-time variable time delay. The improved variable wave method was used for analyzing position tracking performance and stability of the system. Design/methodology/approach - This study consists of both theoretical and real-time operations. Teleoperation systems that provide information about point or environment that people cannot reach and are one of the important robotic works that include the human-machine interaction technology were used to obtain the necessary data. Robots, as the simulated virtual environment to achieve real behaviors, were found to be important for the identification of damage that may occur during the tests performed by real robots and then in terms of prevention of errors identified in algorithm development stages. Findings - The position and speed controls of the real-virtual-real robots consist of the teleoperation system. Also, in this study, the virtual environment was created; variable time delay motion control with teleoperation was performed and applied in the simulation and real-time environment; and the performance results were analyzed. Originality/value - The teleoperation system created in the laboratory consists of a six-degree-of-freedom (dof) master robot, six-dof industrial robot and six-dof virtual robot. A visual interface is designed to provide visual feedback of the virtual robot's movements to the user.
Keywords: Teleoperation; Time delay; Haptic robot; Industrial robot; Improved wave variable method; Virtual robot